Children's Citrus Activity: Diaprepes Root Weevil - Lauren Diepenbrock; Jamie D Burrow (EDIS)
This new two-page children’s activity sheet features pictures of Diaprepes root weevil larva and adults as well as feeding damage. Page two includes a maze. Written by Lauren M. Diepenbrock and Jamie D. Burrow and published by the UF/IFAS Extension 4-H Youth Development program. https://edis.ifas.ufl.edu/4h403